2019
DOI: 10.1002/2211-5463.12611
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Knockdown of lncRNA MNX1‐AS1 suppresses cell proliferation, migration, and invasion in prostate cancer

Abstract: Altered expression of long non‐coding RNA s (lnc RNA s) has been reported in many malignancies, including prostate cancer. However, the role of lnc RNA MNX 1‐ AS 1 in prostate cancer has not been reported. Here, we report that MNX 1‐ AS 1 is expressed in prostate cancer tissues and cells and that si RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…LncRNA MNX1-AS1 was first implicated in the progression of ovarian cancer [ 12 ]. Accumulating evidence demonstrated that MNX1-AS1 played an oncogenic role in multiple malignancies including gastric cancer [ 13 ], esophageal squamous cell carcinoma [ 14 ], osteosarcoma [ 15 ], non-small cell lung cancer [ 16 ], hepatocellular carcinoma [ 17 ], prostate cancer [ 18 ], breast cancer [ 19 ] and cervical cancer [ 20 ] and so on. Although one study reported increased MNX1-AS1 expression in LSCC tissues based on the Cancer Genome Atlas Database (TCGA) analysis [ 21 ], little is known about its role and regulation in the pathogenesis of LSCC.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA MNX1-AS1 was first implicated in the progression of ovarian cancer [ 12 ]. Accumulating evidence demonstrated that MNX1-AS1 played an oncogenic role in multiple malignancies including gastric cancer [ 13 ], esophageal squamous cell carcinoma [ 14 ], osteosarcoma [ 15 ], non-small cell lung cancer [ 16 ], hepatocellular carcinoma [ 17 ], prostate cancer [ 18 ], breast cancer [ 19 ] and cervical cancer [ 20 ] and so on. Although one study reported increased MNX1-AS1 expression in LSCC tissues based on the Cancer Genome Atlas Database (TCGA) analysis [ 21 ], little is known about its role and regulation in the pathogenesis of LSCC.…”
Section: Introductionmentioning
confidence: 99%